Excellent communication skills and empowerment on an employee's job satisfaction - Muthaiyah, Hemalatha; Ahmad Ghazali, Akmar Hayati; Hashim, Norliana (Human Resource Management Academic Research Society, 2023)
The aim of this study is to examine the advantages of excellent communication skills and empowerment on an employee’s job satisfaction. This study was made based on descriptive methods by collecting data analysis results and reports to determine the impact and the influence of demographic factors in communication skills, empowerment, and job satisfaction. Based on descriptive study, the research has developed three main guidelines to create excellent communication skills and effective empowerment which led to a high degree for job satisfaction. Descriptive research method seems to be the most accurate way to conclude a finding in research method. Empowerment seems to be playing a major role in enhancing an employee’s performance and job satisfaction. If a company’s productivity decreases then the cause can be due to many factors such as employees not performing their jobs effectively, personal problems, job dissatisfaction or something else that we need to figure out and get fixed. Employers play an important role in identifying the factors that affect an employee’s productivity. The case study will be based on Kanter's structural empowerment theory. The study will examine the role of access to opportunity, resources, support, and information and two types of power which is formal and informal, as antecedents of job satisfaction. Kanter's structural empowerment theory provides a framework for understanding empowering workplaces and empowered employees. Kantor’s theory has proven to have measurable impact on both employee empowerment and job satisfaction as well as organizational morale and success. This study will be made based on descriptive method by collecting data through survey. The data analysis is formal and quantitative. The respondents are requested to answer the questionnaires on the survey form. Statistical Package for the Social Sciences (SPSS) system will be used to conclude the analysis.